The Work of Religious Extension Workers in Strengthening Religious Moderation in North Tapanuli - Hanna Dewi Aritonang; Tiur Imeldawati; Regina B. M. Nainggolan; Enda Dwi Karina; Luhut Sihombing; Damayanti Br. Hombing (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2023)
The recent rise in cases of intolerance in Indonesia has encouraged the government to make various efforts to maintain religious harmony for the integrity of the Indonesian nation. One of them is through strengthening religious moderation. Religious extension workers are at the forefront of realizing a program to strengthen religious moderation in all work units within the Ministry of Religious Affairs of the Republic of Indonesia, including religious extension workers in North Tapanuli district. The focus of this research is the strategic role of Religious Extension Workers in implementing the strengthening of the religious orientation in the assisted communities, and what efforts have been made by the Ministry of Religious Affairs of North Tapanuli in preparing and empowering religious extension workers as agents or mobilizers religious moderation. This research was conducted by qualitative method. From the research it was found that the presence of religious extension workers in the community is very important to provide counseling and community guidance in caring for plurality and play its role as a driver of strengthening religious moderation.